The pathophysiological and molecular mechanisms of atmospheric PM2.5 affecting cardiovascular health: A review - Feng, Shaolong; Huang, Fangfang; Zhang, Yuqi; Feng, Yashi; Zhang, Ying; Cao, Yunchang; Wang, Xinming (Ecotoxicology and environmental safety, 2023)
Exposure to ambient fine particulate matter (PM2.5, with aerodynamic diameter less than 2.5 µm) is a leading environmental risk factor for global cardiovascular health concern. To provide a roadmap for those new to this field, we reviewed the new insights into the pathophysiological and cellular/molecular mechanisms of PM2.5 responsible for cardiovascular health. Main findings: PM2.5 is able to disrupt multiple physiological barriers integrity and translocate into the systemic circulation and get access to a range of secondary target organs. An ever-growing body of epidemiological and controlled exposure studies has evidenced a causal relationship between PM2.5 exposure and cardiovascular morbidity and mortality. A variety of cellular and molecular biology mechanisms responsible for the detrimental cardiovascular outcomes attributable to PM2.5 exposure have been described, including metabolic activation, oxidative stress, genotoxicity, inflammation, dysregulation of Ca2+ signaling, disturbance of autophagy, and induction of apoptosis, by which PM2.5 exposure impacts the functions and fates of multiple target cells in cardiovascular system or related organs and further alters a series of pathophysiological processes, such as cardiac autonomic nervous system imbalance, increasing blood pressure, metabolic disorder, accelerated atherosclerosis and plaque vulnerability, platelet aggregation and thrombosis, and disruption in cardiac structure and function, ultimately leading to cardiovascular events and death. Therein, oxidative stress and inflammation were suggested to play pivotal roles in those pathophysiological processes. Those biology mechanisms have deepen insights into the etiology, course, prevention and treatment of this public health concern, although the underlying mechanisms have not yet been entirely clarified. [Display omitted] •The effects of ambient PM2.5 on cardiovascular health were overviewed.•The action modes of PM2.5 on cardiovascular system were illustrated.•The advancements in pathophysiological mechanisms were summarized.•The underlying cellular and molecular mechanisms were discussed in detail.